Trough cross-bedded rhodolith limestones in the Atlantic-linked Ronda Basin (Messinian, Southern Spain) - Braga, Juan C.; Aguirre, Julio (Frontiers in Earth Science, 2022)
Rhodolith limestones occur in the upper part of the Miocene infill of the Ronda Basin in southern Spain. This basin was an embayment at the southern margin of the Atlantic-linked Guadalquivir Basin, the foreland basin of the Betic Cordillera. Messinian rhodolith limestones crop out in the mesa of the Roman settlement Acinipo. They mostly consist of trough cross-bedded rhodolith rudstones, which change basinwards to large-scale planar cross bedded rhodolith rudstones, which in turn pass laterally to planar cross-bedded and flat-bedded bryozoan rudstones. Rhodoliths in rudstones are generally broken, exhibiting several phases of breakage and restarted growth of coralline algae. Many rhodoliths also show asymmetrical growth. The rudstone matrix is a packstone with fragments of coralline algae, bryozoans, calcitic bivalves, echinoids, and foraminifers. Large lithoclasts from the basement, heavily bored by bivalves, are common in the rhodolith rudstone, especially in the most massive type. Rhodolith characteristics and sedimentary structures suggest that trough cross-beded rhodolith rudstones accumulated in submarine dunes moved by storm surges in a littoral wedge at the western side of a small bay (the Ruinas de Acinipo bay) in the Ronda Basin. Large-scale planar cross bedded coralline algal and bryozoan rudstones formed in the foresets of the wedge progradation below storm-wave base. The dominance of Lithophyllaceae and Hapalidiales, with scarce representatives of Corallinaceae in the coralline algal assemblages reflects that the Ronda and Guadalquivir basins opened to the Atlantic Ocean.